Notice of a Bond by the Earl of Irvine and other Officers of the Scots Guard of the French King (Louis XIV.), for Expenses of the Corps, &c (Proceedings of the Society of Antiquaries of Scotland, 1862)
A record of two original seventeenth century documents relating to the Scottish Guards of the French King, Louis XIV, one written in French and one in Scots.